Trial of a behavioral intervention to increase dilated fundus examinations in African–Americans aged over 65 years with diabetes. (December 2011) - Casten, Robin J; Brawer, Rickie; Haller, Jullia A; Hark, Lisa A; Henderer, Jeffrey; Leiby, Benjamin; Murchison, Ann P; Plumb, James; Rovner, Barry W; Weiss, David M
This article describes a randomized clinical trial to test the impact of a home-based behavioral activation program to improve rates of dilated fundus examinations in older African–Americans with diabetes. This trial is enrolling subjects who have not met the recommendations for annual eye examinations. The intervention being testing is novel, culturally relevant and has the potential to reduce a significant health disparity regarding vision impairment. Subjects are randomized to behavioral activation or a placebo condition to control for the effects of attention. Both the active and control interventions are delivered in subjects'' homes by a community healthcare worker. The primary outcome is whether a subject had a dilated fundus examination by an ophthalmologist by 6 months.